Analysis of the development of competencies in subjects related to materials science through the software Ansys Granta EduPack® in Brazilian Portuguese - Júlio Cesar Dutra; Jacqueline Matsuda Augustini (The Journal of Engineering and Exact Sciences)
Theories in the educational area are constantly evolving. Learning theories, knowledge images and competencies are ideas frequently used in teaching; this is not different in engineering education curricula. Many computational resources that help education are now available, and one of them is Ansys Granta EduPack®, a tool that aids engineering students in materials selection, among other activities. Even though this may be especially useful, the language used may cause some difficulties. The influence of using this software in both languages, English and Portuguese, was investigated with two groups of students attending Metallic Materials from an undergraduate mechanical engineering course at Centro Universitário FEI. They were monitored for one semester to study the development of their competencies by using learning theories and knowledge images. This software was translated into Brazilian Portuguese and was used in laboratory classes, allowing both the analysis of the influence of the language on the development of competencies and the knowledge acquired throughout the semester. This was based on what students said, and it was noticed that the translated version has its advantages, allowing the students to focus on the assignment proposed and on the usage of the knowledge acquired, even those who are English fluent. It was also found that the use of different tools is necessary for the development of competencies.